1992
DOI: 10.1070/pu1992v035n05abeh002239
|View full text |Cite
|
Sign up to set email alerts
|

German Stepanovich Zhdanov (Obituary)

Abstract: Numerical instabilities hamper the computer simulation of axially symmetric, three-dimensional transient discharges from proceeding (Davies et al 1977).In the present paper, a method is presented in which suppression of the instabilities is attempted by avoiding numerical differentiation. The results when the present method is applied to simulation of a narrow, high-overvoltage discharge observed by Chalmers et al (1972) show that this method enables one to trace the cathode streamer reaching the cathode and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Redistribution of the charge carriers between impurity-induced and radiation defect states and allowed bands makes it possible to vary the concentration of the free charge carriers and to realize metal-insulator-type transitions induced by electron irradiation. For example, it was shown that electron irradiation of the undoped p-Pb 1−x Sn x Te alloys causes a decrease in the free hole concentration and a transition to the insulating state due to the generation of electrically active n-and p-type defects and the flow of electrons from the radiation donor level to the valence band [9].…”
Section: Introductionmentioning
confidence: 99%
“…Redistribution of the charge carriers between impurity-induced and radiation defect states and allowed bands makes it possible to vary the concentration of the free charge carriers and to realize metal-insulator-type transitions induced by electron irradiation. For example, it was shown that electron irradiation of the undoped p-Pb 1−x Sn x Te alloys causes a decrease in the free hole concentration and a transition to the insulating state due to the generation of electrically active n-and p-type defects and the flow of electrons from the radiation donor level to the valence band [9].…”
Section: Introductionmentioning
confidence: 99%